PEGylated dihydromyricetin-loaded nanoliposomes coated with tea saponin inhibit bacterial oxidative respiration and energy metabolism. Issue 19 (12th August 2021) - Luo, Fan; Zeng, Dandan; Chen, Renxiang; Zafar, Ayesha; Weng, Ling; Wang, Wenxiong; Tian, Yubo; Hasan, Murtaza; Shu, Xugang
Abstract : Preparation and bacteria therapeutic mechanism of CS/CTS@DMY-lips. Abstract : The biofilms produced by the aggregation of bacterial colonies are among the major obstacles of host immune system monitoring and antimicrobial treatment. Herein, we report PEGylated dihydromyricetin-loaded liposomes coated with tea saponin grafted on chitosan (TS/CTS@DMY-lips) as an efficient cationic antibacterial agent against Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ), which is supported by their deep penetration into bacterial biofilms and broad pH-stable release performance of dihydromyricetin (DMY). The successful construction of the drug delivery system relied on tea saponin grafted on chitosan (TS/CTS) via formatted ester bonds or amido bonds as a polyelectrolyte layer of PEGylated dihydromyricetin-loaded liposomes (DMY lips), which achieved controlled release of DMY in weak acidic and neutral physiological environments. The micromorphology of TS/CTS@DMY-lips was observed to resemble dendritic cells with an average size of 266.49 nm, and they had excellent encapsulation efficiency (41.93%), water-solubility and stability in aqueous solution. Besides, TS/CTS@DMY-lips displayed effective destruction of bacterial energy metabolism and cytoplasmic membranes, resulting in the deformation of the cell wall and leaking of cytoplasmic constituents. Compared to free DMY, DMY lips and chitosan-coated dihydromyricetin liposomes (CTS@DMY-lips), TS/CTS@DMY-lips has more thorough killing activity against E. coli and S. aureus, which is related to its excellent sustained release performance of DMY under the protection of the TS/CTS coating.